A Pendekatan Experiential Learning Berbasis Kajian Budaya untuk Meningkatkan Keterampilan Menulis dan Literasi Kritis - Rizal Fauzi; Minhatul Ma’arif (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the effectiveness of Culture-Based Experiential Learning in improving writing skills and critical literacy among students of the English Language Education Study Program at Universitas Serang Raya. The background of this research stems from the low level of students’ academic writing abilities, which often fail to reflect critical awareness of social and cultural contexts. The Experiential Learning approach was chosen because it emphasizes direct experience, reflection, conceptualization, and active application components that align with the needs of culturally contextualized writing instruction. This research employs a mixed-methods approach with a sequential explanatory design, involving 15 students enrolled in the Basic Writing course for one semester. Quantitative data were obtained through pre- and post-tests to measure improvements in writing skills, while qualitative data were collected through observations, interviews, and students’ reflective journals. The results indicate an average improvement of 26% in writing skills, with the highest increases observed in critical reflection (34%) and cultural theory integration (29%). Qualitative analysis reveals that direct experiences in observing and writing about cultural phenomena strengthened students’ reflective, argumentative, and contextual thinking abilities. The study concludes that integrating cultural studies within the Experiential Learning cycle fosters a more meaningful, contextual, and critical writing process. These findings offer significant implications for the development of writing pedagogy in higher education, particularly within English language learning contexts that emphasize critical literacy and cultural awareness.